Plantão educativo para a prevenção de DST/HIV/AIDS com adolescentes escolares - Costa, Ana Cristina Pereira de Jesus (2013)
In the panorama of STD / HIV / AIDS among adolescents, the strategy is to control the transmission prevention in order to promote their health. From the perspective of implementing new strategies, considering the characteristics of adolescence, their vulnerability, and lack of educational long term was used in this study, a new proposal adopted in school: the duty of the individual educational teenager. The objective of this research was to evaluate the application of a duty education on STD / HIV / AIDS with adolescents from a public school in Imperatriz - MA. Intervention research, quasi-experimental, quantiqualitative, with a longitudinal design. Were evaluated 250 adolescent students between January and June 2013 in three stages. At first, the adolescents completed an instrument of knowledge, behaviors and attitudes of STD / HIV / AIDS before attending the educational intervention. In the second stage, students participated in educational duty. In the third stage, adolescents responded again an instrument to assess whether there was a change in knowledge, attitudes and behaviors related to STD / HIV / AIDS, 30 days after the educational intervention. Analyzed in stratified sample sociodemographic characteristics, knowledge of adolescents regarding the access and use of health services, the sources of information used on STD / HIV / AIDS, and the knowledge, behaviors and attitudes regarding safe sex practices forward to STD / HIV / AIDS before and after the educational intervention. The data were analyzed with statistical software STATA version 8.0. Adolescents have an average of 15.5 years of age, are unmarried (as) without a partner (a) fixed (75.6 %), predominantly female (52.4 %) and family income between one and three minimum wages (46 %). There were trends proportional increase was statistically significant by gender (p - value = 0.00), indicating higher levels of parental education of boys. There was a statistically significant increasing trend with respect to sex of respondents (p - value = 0.02), indicating lower household income among girls. Most students have no indication of health services by the school (79.6 %). The main sources of information outside of school on STD / HIV / AIDS are radio / TV / newspaper (54 %). Adolescents increased knowledge about the symptoms (99.2 %), the modes of transmission of AIDS (100 %) and the use of condoms to prevent STD / HIV / AIDS (100 %). Substantial portion of adolescents (98.4 %) believe have no chance of acquiring HIV. Those who have sexual activity have a partner (56.3 %) and condom use at last intercourse (65.7 %). Adolescents evaluated the educational duty as very good (77.6 %) reported having changed the knowledge and behaviors related to STD / AIDS to better (79.6 %) and maintain the use of condoms during sexual intercourse. Therefore, the shift in school education can be considered a new strategy of health education; it increased in adolescent’s knowledge and adherence to healthy behaviors for the prevention of STD / HIV / AIDS.